Rock mass change monitoring in a sill pillar at Vale's Coleman mine (Sudbury, Canada) - Valley, Benoît; Milkereit, Bernd; Pun, Winnie; Pilz, Marco; Hutchinson, Jean; Delaloye, Dani; Madjdabadi, Behrad M.; Dusseault, Maurice; Thibodeau, Denis; Forsythe, Anneta (My University, 2012)
Optimization of the mining sequence in terms of economics (maximizing net present value) often leads to multi-front mining methods generating pillars. Significant resources are tied up in these pillars, but mining them is often challenging. In order to improve our understanding of rock mass behaviour while extracting these pillars, an extensive monitoring program has been designed and implemented at Vale’s Coleman mine (Sudbury, Canada). The program focuses on existing and new technologies that have potential for monitoring deformation and rock mass property changes. It includes both active and passive methods: gravimeters, multi-point borehole extensometers, fiber optic strain meters, fixed and portable three-component seismic arrays, borehole imaging and sonic logging, and, repeated LiDAR surveys. This paper reports results from an initial project phase, when only a small amount of mining has taken place. The goal was to test and compare technologies in order to assess their sensitivity, accuracy, repeatability and suitability for underground mining conditions. Value is gained by having a broad range of monitoring devices running side by side, enabling comparisons and benchmarking.
, 2012